STUDI KOMPARATIF TENTANG PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA MTs YANG MEMPEROLEH PEMBELAJARANDENGAN PENDEKATAN PROBLEM POSING DAN PEMBELAJARAN LANGSUNG - Trisnawati, Rini; Wahyudin; Kusnandi (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2017)
This study aims to examine enhancement of critical thinking ability of the students who got learning with problem posing approach and the students who got direct instruction. This study employed experimental research with Pretest-Post-test two treatment design. The population in this study were class VIII the students of one MTsN in Pekanbaru. For sample for this study, two classes were taken as experimental class by using purposive sampling technique. The instruments which were used were in the forms of critical thinking ability tests. The findings of this study were: (1) Critical thinking ability of the students who get learning with Problem Posing approach was better than the students who got Direct Instruction and (2) The enhancement of mathematical critical thinking ability of the students who got learning with Problem Posing approach was better than the students who got Direct Instruction.